Analisis Akseptor KB Dalam Penggunaan Alat Kontrasepsi Dalam Rahim (AKDR) di Puskesmas Perumnas Kabupaten Lahat Tahun 2021 - Rahma Dewi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The intrauterine device (IUD) is an effective contraceptive. The Perumnas Public Health Center in Lahat Regency is one of the health centers with a low IUD usage coverage (1.3%) below the set target (25%). This study aims to analyze the factors that influence family planning acceptors in using the IUD. This research is an analytic survey with a cross-sectional approach. The sample was taken by simple random sampling with a total of 100 respondents in women of childbearing age (WUS) in the area of ??the Public Health Center of Lahat Regency. Bivariate analysis showed that parity (p=0.002, OR=2.825, 95%CI=1.225-6.492), knowledge (p=0.003, OR=3.467, 95%CI=1.521-7.905), the role of health workers (p=0.001, OR=3.930, 95%CI=1.688-9.154), husband's support (p=0.016, OR=2.681, 95%CI=1.191-6.032) had a significant relationship with IUD use. Age, education level and attitude were not related to IUD use (p>0.05). Multivariate analysis showed mother's knowledge was the most significant factor associated with IUD use. The low use of IUDs was due to the high proportion of mothers who had less knowledge (64.2%) and the high proportion of mothers who did not receive husband's support (63.0%). This is due to the lack of a role for health workers to provide education and information about the IUD to mothers and husbands. The Puskesmas should socialize and motivate mothers to use the IUD.